Pengaruh Profitabilitas, Stuktur Modal dan Ukuran Perusahaan Terhadap Nilai Perusahaan Melalui Kebijakan Dividen Sebagai Variabel Intervening pada Perusahaan Food & Beverage yang Terdaftar di BEI Periode 2020-2024 - Anzari, Aulia Rahman; Elfiswandi, Elfiswandi; Pratiwi, Hanna (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to analyse the effect of profitability, capital structure, and company size on company value with dividend policy as an intervening variable in companies in the Food and Beverage sub-sector listed on the Indonesia Stock Exchange for the period 2020–2024. The study uses a quantitative causal approach with a sample of 18 companies selected through purposive sampling. The data, in the form of annual financial reports, were analysed using multiple linear regression and path analysis to test the direct and indirect effects between variables. Profitability was proxied by Return on Assets, capital structure by Debt to Equity Ratio, company size by the natural logarithm of total assets, dividend policy by Dividend Payout Ratio, and company value by Price to Book Value. The results show that profitability has a significant effect on company value, while capital structure and company size show varying effects. Dividend policy is proven to act as an intervening variable that strengthens the relationship between financial performance and company value. These findings emphasise the importance of financial performance management and dividend policy in increasing company value and investor confidence.